Transcription alterations of members of the ubiquitin–proteasome network in prostate carcinoma - Hellwinkel, O J C; Asong, L E; Rogmann, J-P; Sültmann, H; Wagner, C; Schlomm, T; Eichelberg, C (Prostate cancer and prostatic diseases, 2011)
The purpose of this work was to investigate the role of the ubiquitin–proteasome network (UPN) in prostate cancer (PCA) and to elicit potential markers for this disease. The UPN represents a key factor in the maintenance of cellular homoeostasis as a result of its fundamental function in the regulation of intracellular protein degradation. Members of this network have a role in the biology of haematological and solid tumours. Tumour cells and normal epithelial cells from 22 prostatectomy specimens were isolated by laser microdissection. Prostate biopsy samples from healthy individuals served for technical calibration and as controls. Transcript levels of eight selected genes with E3 ubiquitin ligase activity (labelling target proteins for proteasome degradation) and two genes belonging to the proteasome–multienzyme complex itself were analysed by quantitative real-time RT-PCR. The proteasome genes PSMC4 and PSMB5 and the E3 ubiquitin ligase NEDD4L were significantly and coherently upregulated in PCA cells compared with the corresponding adjacent normal prostate tissue. Transcription of the E3 ubiquitin ligase SMURF2 was significantly higher in organ-confined tumours (pT2) compared with non-organ-confined cancers (pT3). The results indicate a role for PSMC4 and PSMB5 and the E3 ubiquitin ligase NEDD4L in prostate tumourigenesis, whereas SMURF2 downregulation could be associated with clinical progression. NEDD4L and SMURF2 both target transforming growth factor (TGF)-β for degradation. This reflects the pleiotropic role of the TGF-β signalling pathway acting as a tumour suppressor in normal and pre-cancerous cells, but having oncogenic properties in progressing cancer. Further studies have to elucidate whether these alterations could represent clinically relevant PCA-diagnostic and progression markers.